2014
DOI: 10.2147/oajsm.s63540
|View full text |Cite
|
Sign up to set email alerts
|

Injuries and disorders among young ice skaters: relationship with generalized joint laxity and tightness

Abstract: This study retrospectively investigated 192 teenage speed and figure skaters with prior injuries documented by an athletes’ questionnaire, who underwent a physical examination to assess their muscle tightness and generalized joint laxity. In all athletes, the degree of muscle tightness and joint laxity were measured by a standardized physical examination. A descriptive report of the types of injuries showed a predominance of fractures, ligament injuries, enthesitis, and lower back pain. Approximately 5% of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 28 publications
1
29
0
1
Order By: Relevance
“…20 Also, Okamura and colleagues found a significant relationship between low back pain and generalized ligamentous laxity in 192 men who were ice skating athletes in Japan. 21 Our reults are consistent with these studies since the prevalence of musculoskeletal injuries was significantly higher in those who had generalized ligamentous laxity. Tobias and colleagues studied 2901 adolescents with an average age of 13.8 years old.…”
Section: Tablesupporting
confidence: 90%
“…20 Also, Okamura and colleagues found a significant relationship between low back pain and generalized ligamentous laxity in 192 men who were ice skating athletes in Japan. 21 Our reults are consistent with these studies since the prevalence of musculoskeletal injuries was significantly higher in those who had generalized ligamentous laxity. Tobias and colleagues studied 2901 adolescents with an average age of 13.8 years old.…”
Section: Tablesupporting
confidence: 90%
“…Injuries typically happen when the skater falls in the curves (ie, sliding under the paddings), in collisions with competing skaters or as a self-inflicted injury (ie, the blade hits the lower extremity) 22. Commonly reported injuries include fractures, ligament injuries, tendinopathies and lower back pain 23. Lacerations to the lower extremities have been reported from time to time 24 25.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported the influence of trunk flexibility on LBP. [2][3][4][5][6] Hence, we considered that a reduction in trunk flexibility might be associated with repeated micro-trauma and excessive stress at the lumbar vertebra as a bone stress reaction. 15 We focused on a reduction in the flexibility of pelvic area muscle groups, as an essential aspect of compensation for a reduction in trunk flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some previous studies have reported a relationship between LBP and hip flexibility. [2][3][4][5][6] We doubted that stress fracture might have occurred as a result of repeated stress to the lumbar vertebrae. Perhaps reduced trunk flexibility might be compensated by changes in the lumbar vertebrae.…”
Section: Introductionmentioning
confidence: 99%